Direct quantitative indices for ripening of olive oil fruits to predict harvest time. Issue 8 (27th November 2015) - Trapani, Serena; Migliorini, Marzia; Cherubini, Chiara; Cecchi, Lorenzo; Canuti, Valentina; Fia, Giovanna; Zanoni, Bruno
Abstract : The aim of this work was both the monitoring of selected indices, directly connected to biochemical phenomena of olive oil fruit ripening, and the processing of experimental results to choose the most appropriate harvesting time for olives. Two different olive cultivars ( Frantoio and Moraiolo ) in two different olive orchards were studied, picking olives by hand once a week from the beginning of September to the beginning of December. Olive samples were analyzed for average weight, pulp/stone ratio, and Maturity Index. A homogeneous batch of olives was crushed, and the olive paste was used for the measurement of water, oil, sugar, and phenolic compounds contents in olive oil fruits. Formally similar kinetics of oil and sugar contents were obtained for both studied cultivars and orchards. Oil contents showed an increasing sigmoidal trend tending to an asymptote; sugar contents showed an opposite behavior with a decreasing sigmoidal trend tending to an asymptote. The total phenolic compounds content showed a decreasing trend during ripening. The secoiridoids oleuropein aglycon and oleuropein were among the most abundant phenolic compounds. Their contents showed a linear decrease during olive ripening, modelled by a significant pseudo‐zero order kinetics; trends were cultivar‐dependent, though similar for both orchards. Practical applications: Both monitoring and processing of chemical ripening indices in olive oil fruits may be useful to define an adequate ripening degree and to predict harvest time. Modeling of oil and sugar content kinetics during ripening may improve the prediction approach to harvesting time of olive oil fruits, as compared to the common Maturity Index method. For instance, the harvest target of maximizing processing yield may be attained on the basis of the following phenomenological evidence: A constant maximum value for oil content corresponds to attainment of a constant minimum value of sugar content. A sensible choice of the most appropriate harvesting time for olives may be made by performing a combined evaluation of kinetics for oil, sugar, and phenolic compounds contents. An example to understand how a change in harvesting time may affect olive composition and, potentially, the quality of oil to be extracted, was reported in this paper. An example of combined kinetic trends of the sugar (·····), oil (—), and oleuropein (‐‐‐‐) contents to choose the harvesting time of olive oil fruits for Frantoio cultivar on one of the orchards studied. Abstract : An example of combined kinetic trends of the sugar (·····), oil (—), and oleuropein (‐‐‐‐) contents to choose the harvesting time of olive oil fruits for Frantoio cultivar on one of the orchards studied.